Application of Advanced Hydrology Tools of Geographic Information System (GIS) for field Level Design of a Drop Structure - Purnima Mishra; R, Ravi Babu (Journal of Soil and Water Conservation, 2022)
Recent advances in GIS could be effectively used in identification of suitable sites, delineation of catchment areas, estimation of runoff and proper design of different soil and water conservation structures. In the present study, an attempt was made to delineate the catchment of a proposed drop structure in an agricultural micro-watershed in Kashipur block of Purulia district using hydrology modelling extension tools available in ArcGIS 9. The runoff for the desired return period was estimated using an integrated approach of GIS based hydrology modelling extension tools and Soil Conservation Service-Curve Number (SCS-CN) model and thereafter the structure was designed taking into account the site conditions. The study revealed that GIS based catchment delineation and runoff estimation is highly useful in design of expensive soil and water conservation engineering structures.